2019
DOI: 10.1111/bjep.12281
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the instructional quality of private tutoring and its effects on student outcomes: Analyses from the German National Educational Panel Study

Abstract: Background.A considerable proportion of secondary school students gets additional support from private tutoring lessons. Empirical findings on the effectiveness of private tutoring are inconclusive. The instructional quality of the tutoring lessons might influence their effectiveness.Aims. We analysed (1) whether students privately tutored in the subjects German or mathematics outperformed their non-tutored counterparts; (2) whether the instructional quality of the tutoring lessons can be described with the th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
2
10

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 42 publications
1
36
2
10
Order By: Relevance
“…Some studies report considerable effects of household income on SE participation (Hille et al, 2016;Schneider, 2005), while others report no such effects (Abele & Liebau, 1998;Guill & Lintorf, 2019;Luplow & Schneider, 2014). Similarly, some studies found that academic parents tend to not send their children to SE in Germany (Entrich & Lauterbach, 2019;Hille et al, 2016;Luplow & Schneider, 2014;Schneider, 2005), while others reported a significantly higher likelihood of children with academic parents to obtain SE (Guill & Lintorf, 2019;Guill, Lüdtke, & Köller, 2020). We suspect that the differences in the effect of the SES of the students are related to the measurement of the variables and the construction of the models.…”
Section: Shadow Education As Ses-specific Investment?mentioning
confidence: 84%
“…Some studies report considerable effects of household income on SE participation (Hille et al, 2016;Schneider, 2005), while others report no such effects (Abele & Liebau, 1998;Guill & Lintorf, 2019;Luplow & Schneider, 2014). Similarly, some studies found that academic parents tend to not send their children to SE in Germany (Entrich & Lauterbach, 2019;Hille et al, 2016;Luplow & Schneider, 2014;Schneider, 2005), while others reported a significantly higher likelihood of children with academic parents to obtain SE (Guill & Lintorf, 2019;Guill, Lüdtke, & Köller, 2020). We suspect that the differences in the effect of the SES of the students are related to the measurement of the variables and the construction of the models.…”
Section: Shadow Education As Ses-specific Investment?mentioning
confidence: 84%
“…However, to make reliable statements about the impact of the respective SES gap in access to SE in a society on educational and social inequality, national panel data are necessary (e.g. Buchmann et al, 2010; Guill et al, 2019; Stevenson and Baker, 1992). For analyses to be more meaningful, a stronger focus on and differentiation into vertical and horizontal educational outcomes by measuring the long-term effects of SE on post-secondary educational attainment, labor market outcomes, and further supplementary education investments (as suggested by Entrich and Byun, in press) is needed.…”
Section: Discussionmentioning
confidence: 99%
“…In countries with highly remedial modal use of SE, such positive effects are seldom reported (Buchmann et al, 2010) and often highly doubted that there are any such effects at all (e.g. Guill et al, 2019). 2.…”
Section: Fundingmentioning
confidence: 99%
“…(Choi and Park, 2016), especially the internal variables of students' mathematical learning. The quality or the characteristic of PT participation, such as the length of PT lessons, class-size, instructional content, and quality of instruction (Guill et al, 2019), should be considered. So that, future study, a more comprehensive system of variables were needed to deeply model the decisionmaking process, and also more qualitative studies were needed to supplement the large size quantitative analysis.…”
Section: Discussionmentioning
confidence: 99%